The Interplay of Nutrition, the Gut Microbiota and Immunity and Its Contribution to Human Disease - Samantha L. Dawson; Emma Todd; Alister C. Ward (Biomedicines)
Nutrition, the gut microbiota and immunity are all important factors in the maintenance of health. However, there is a growing realization of the complex interplay between these elements coalescing in a nutrition–gut microbiota–immunity axis. This regulatory axis is critical for health with disruption being implicated in a broad range of diseases, including autoimmune disorders, allergies and mental health disorders. This new perspective continues to underpin a growing number of innovative therapeutic strategies targeting different elements of this axis to treat relevant diseases. This review describes the inter-relationships between nutrition, the gut microbiota and immunity. It then details several human diseases where disruption of the nutrition–gut microbiota–immunity axis has been identified and presents examples of how the various elements may be targeted therapeutically as alternate treatment strategies for these diseases.